The Function of Wnt Ligands on Osteocyte and Bone Remodeling. (July 2019) - Du, J.H.; Lin, S.X.; Wu, X.L.; Yang, S.M.; Cao, L.Y.; Zheng, A.; Wu, J.N.; Jiang, X.Q.
Bone homeostasis is continually maintained by the process of bone remodeling throughout life. Recent studies have demonstrated that Wnt signaling pathways play a fundamental role in the process of bone homeostasis and remodeling. Intracellular Wnt signaling cascades are initially triggered by a Wnt ligand–receptor complex formation. In previous studies, the blocking of Wnt ligands from different osteoblastic differentiation stages could cause defective bone development at an early stage. Osteocytes, the most abundant and long-lived type of bone cell, are a crucial orchestrator of bone remodeling. However, the role of Wnt ligands on osteocyte and bone remodeling remains unclear. In our present study, we found that, besides osteoblasts, osteocytes also express multiple Wnt ligands in the bone environment. Then, we used a Dmp1-Cre mouse line, in which there is expression in a subset of osteoblasts but mainly osteocytes, to study the function of Wnt ligands on osteocyte and bone remodeling in vivo. Furthermore, we explored the role of Wnt ligands on osteocytic mineralization ability, as well as the regulatory function of osteocytes on the process of osteoblastic differentiation and osteoclastic migration and maturity in vitro. We concluded that Wnt proteins play an important regulatory role in 1) the process of perilacunar/canalicular remodeling, as mediated by osteocytes, and 2) the balance of osteogenesis and bone resorption at the bone surface, as mediated by osteoblasts and osteoclasts, at least partly through the canonical Wnt/β-catenin signaling pathway and the OPG/RANKL signaling pathway.